Technology and the Early Modern Self - Cohen, A. author. aut Link
XII, 268 p. 13 illus.
Keywords: Cohen utilizes the interdisciplinary nature of contemporary literary and cultural studies to shed new light on the relationships between technologies and the people who used them during the early modern period.